Description of Student Learning Outcomes between the Students who Follow Guidance Learning Outside the School with The Students are not Follow it in Biology Topics Class XI Science SMAN 7 Padang - Fauzia Mawaddah; Rahmawati Darussyamsu; Helendra Helendra (Bioeducation Journal, 2018)
Factors influencing the success of a learning can come from both internal and external. Learners tend to have concerns in implementing learning to achieve good learning outcomes, so learners want to increase learning outside the school. Today, there are a lot of learning counseling institutions that are developing in various regions in Indonesia. This leads to a lot of interest of learners to follow the guidance of learning outside school. The purpose of this study is to see the contribution of tutoring outside school to the learning outcomes of learners who follow the guidance of learning outside the school on the subjects of biology class XI Science SMAN 7 Padang. The population of this research is all students of class XI IPA SMAN 7 Padang. Research samples are learners who follow and learners who do not follow the guidance of biological learning outside the school. The sampling technique used saturation sampling technique. The data analysis technique used is the median test, because one of the data is not normally distributed and the two groups are homogeneous. The average learning outcomes of learners that is 86.91, not too significant difference with those who do not follow the guidance of learning outside the school with an average of 84.88. The result of data analysis shows that there is no contribution of learning guidance to learners' learning outcomes which follow the guidance of study outside school with comparison of X2 count 0,270 and X2 table 3,84, so X2 count <X2 table. Thus, it can be concluded that the guidance of learning outside the school does not contribute to the learning outcomes of learners on the subjects of biology class XI IPA SMAN 7 Padang.